2022
DOI: 10.1007/s00415-022-11173-0
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis in stroke patients with elevated inflammatory markers

Abstract: Objective To investigate the prognostic value of white blood cell count (WBC) on functional outcome, mortality and bleeding risk in stroke patients treated with intravenous thrombolysis (IVT). Methods In this prospective multicenter study from the TRISP registry, we assessed the association between WBC on admission and 3-month poor outcome (modified Rankin Scale 3–6), mortality and occurrence of symptomatic intracranial hemorrhage (sICH; ECASS-II-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…Therefore, they could better reflect the inflammatory status than a single inflammatory cell count. Previous studies in patients with ac-LVO suggested that leukocytes, neutrophils, and NLR were associated with 90 day prognosis regardless of whether patients received EVT 28 29. In our study, the results were consistent with the above results, suggesting that the association between inflammation indicators and prognosis did not change much in posterior circulation stroke.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, they could better reflect the inflammatory status than a single inflammatory cell count. Previous studies in patients with ac-LVO suggested that leukocytes, neutrophils, and NLR were associated with 90 day prognosis regardless of whether patients received EVT 28 29. In our study, the results were consistent with the above results, suggesting that the association between inflammation indicators and prognosis did not change much in posterior circulation stroke.…”
Section: Discussionsupporting
confidence: 92%
“…Except for the unexpectedly high rates of ICH after IVT in patients with tumors of the pituitary region, the rates of symptomatic ICH in the other patient groups with intracranial neoplasms (Table 5) seemed to be in the upper range of the rates of symptomatic ICH reported in other studies of patients with ischemic stroke within the TRISP cooperation ranging between 4% and 6%. [14][15][16] Due to the heterogeneity of imaging modalities and lack of availability of MRI for all patients, beyond the assessment of intratumoral hemorrhage, we did not differentiate whether any ICH after IVT occurred distant from the ischemic area, which were reported in 3% of patients, with approximately half of them classified as symptomatic ICH, in a cohort with MRI available. 17 However, although limited by the overall sample size, the relatively high rate of 4% fatal ICH after IVT in patients with meningioma is striking.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with meningioma or intra-axial primary brain tumors, functional outcome was comparable with that of previous analysis within the TRISP cooperation (Table 5). [14][15][16]21 The strengths of our study include the multicenter approach with a detailed characterization of clinical and imaging data of stroke patients with intracranial tumors after IVT. Compared with previous reports, we present the analysis of a large cohort of patients that is commonly excluded from clinical trials related to IVT and that does not routinely receive IVT in clinical practice neither.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations